Collision-induced stimulated photon echo on the broad spectral line. (30th November 2016) - Reshetov, V A
Abstract: The collision-induced stimulated photon echo formed on the broad spectral line on the transition with the angular momentum change J a = 0 → J b = 1 is studied theoretically. The dependencies of the echo intensity on the areas of exciting pulses and on the strength of the external magnetic field under the conditions of experiments in ytterbium ( 174 Yb) vapor are obtained. The ways to measure orientation and alignment relaxation rates of the excited atomic level are discussed.